Microscopical Study Of Plant "Dipteracanthus Prostratus Poir-Acanthaceae" - C. IYYAPPAN; V.M. MOUNNISSAMY (International Journal of Pharma and Bio Sciences, 2011)
The present paper deals with the microscopical study of leaf and stem of Dipteracanthus prostrates (poir.), Acanthaceae, for its identification and to distinguish it from the co-existing weeds and adulterants.